Optical nanorod antennas modeled as cavities for dipolar emitters: Evolution of sub- and super-radiant modes - Taminiau, Tim H. (2011)
Optical antennas link objects to light. Here we derive an analytical model for the interaction of dipolar transitions with radiation through nanorod antenna modes, by modeling nanorods as cavities. The model includes radiation damping, accurately describes the complete emission process, and is summarized in a phase-matching equation. We analytically discuss the quantitative evolution of antenna modes, in particular the gradual emergence of subradiant, super-radiant, and dark modes, as antennas become increasingly more bound, i.e., plasmonic. Our description is valid for the interaction of nanorods with light in general and is thus widely applicable.